Reconceptualizing Mandatory Bequests for Children of Unregistered Marriages: Islamic Family Law Responses to Supreme Court Circular Letter No. 3 of 2023 - Riskanda, Yilda; Zulkifli; Putri, Dewi; Raus, Afrian; Effendi, Amri (UIN Mahmud Yunus Batusangkar, 2025)
This study examines the application of the mandatory will (wasiat wajibah) as regulated in Supreme Court Circular Letter (SEMA) No. 3 of 2023, particularly in relation to children born from valid but legally unregistered marriages. The research aims to analyze the legal construction and implications of SEMA No. 3 of 2023 concerning inheritance rights through mandatory wills within the framework of Islamic inheritance law in Indonesia. This research adopts a library-based methodology using a normative juridical approach, focusing on statutory analysis of SEMA No. 3 of 2023 as the primary legal source. Secondary data are derived from books, scholarly articles, and relevant scientific works. Data analysis is conducted through deductive reasoning, while data validity is ensured through source triangulation.The findings indicate that wasiat wajibah under SEMA No. 3 of 2023 serves as an alternative legal instrument to provide inheritance shares to children who are not formally recognized as heirs under classical Islamic inheritance law. This provision extends the earlier application of mandatory wills, previously limited to adopted children under Article 209 of the Compilation of Islamic Law. Although the inheritance portion through wasiat wajibah is limited to one-third of the estate, this policy reflects the principle of maṣlaḥah and the best interests of the child by ensuring minimum economic protection and legal certainty for children born from unregistered marriages.